PREVALENCE OF MANGE MITE INFESTATION ON DOGS IN BALI BY TAPE STRIP METHOD - Nazara, Nonitema; Oka, Ida Bagus Made; Dwinata, I Made (Buletin Veteriner Udayana, 2023)
Mange is a disorder of the skin that can cause displeasure and changes in the skin. Scurvy is caused by Sarcoptes scabiei and Demodex spp . The number of dermatitis events in dogs is caused by maintenance management by removing which may be able to contact with dogs with mange. The purpose of this study was to find out the prevalence of mange mite infestations, the type of mite, and its relationship to risk factors that influence infestations in dogs in Bali. The number of study samples was 100 dogs in Bali that showed clinical symptoms in the form of disobedience which was distinguished by age, race, gender, and way of maintenance. The dog selected as a diselotip sample is then examined with a microscope to identify the mites. A dog sample tests positive if at least one mite is found. The results showed the prevalence of mange mites in dogs in Bali was 22% consisting of Sarcoptes scabiei 10% and Demodex spp. 12%. Further identification found Demodex canis with a prevalence of 7% and Demodex cornei 5%. The Chi-square test found that age and way of maintenance had a prevalence relationship between mite infestations, while gender and race were not associated with the prevalence of mite infestations. In connection with the large prevalence, serious attention is needed for dogs kept in Bali, especially regarding skin hygiene and health.